Intensified conditioning regimens improved disease‐free survival and engraftment after unrelated single‐unit cord blood transplantation but not after matched sibling or matched unrelated donor allogeneic hematopoietic cell transplantation. Issue 1 (31st October 2022) - Konuma, Takaaki; Kanda, Junya; Uchida, Naoyuki; Nishijima, Akihiko; Tanaka, Masatsugu; Ozawa, Yukiyasu; Sawa, Masashi; Onizuka, Makoto; Ota, Shuichi; Maruyama, Yumiko; Kanda, Yoshinobu; Kawakita, Toshiro; et al.
Abstract: The impact of conditioning intensity on different donor groups has been unclear in allogeneic transplantation. The objective of this study was to clarify the effect of conditioning intensity on disease‐free survival (DFS), relapse, non‐relapse mortality (NRM), neutrophil engraftment, and graft‐versus‐host disease for each donor type. We retrospectively evaluated the effect of conditioning intensity on transplant outcomes for patients with acute leukemia or myelodysplastic syndrome aged between 16 and 60 years in Japan using the transplant conditioning intensity (TCI) scoring system. A total of 8526 patients who received first allogeneic transplantation from 6/6 antigen‐matched sibling donor (MSD, n = 2768), 8/8 allele‐matched unrelated donor (MUD, n = 2357), and unrelated single‐cord blood (UCB, n = 3401) were eligible for the analyses. Compared to conditioning with TCI score 4.0, which was corresponds to conventional myeloablative conditioning, including cyclophosphamide with total body irradiation 12 Gy or busulfan 12.8 mg, and was considered as the reference group in the multivariate analyses, intensified conditioning with TCI score ≥4.5 improved DFS (hazard ratio [HR], 0.81, P < 0.001) and relapse rate (HR, 0.70, P < 0.001) but only after UCB transplants and not MSD and MUD transplants. In contrast, NRM was higher after intensified conditioning with TCI score ≥4.5 for MSD (HR, 1.39, P = 0.008) and MUD (HR, 1.47, P = 0.002) transplants but not UCB transplants (HR, 1.12, P = 0.240). Neutrophil engraftment was also significantly higher after intensified conditioning with TCI score ≥4.5 but only for UCB transplants (HR, 1.24, P < 0.001), whereas it was significantly lower after reduced‐intensity conditioning with TCI score ≤3.5 for MSD transplants only (HR, 0.82, P < 0.001). These data demonstrated that an intensified conditioning regimen improved survival and engraftment rate only after a UCB transplants. Therefore, TCI scoring system could enable the optimization of conditioning intensity according to donor type, particularly in terms of survival and engraftment.